Age-related function of tumor suppressor gene TP53:contribution to cancer risk and progression - Cherdyntseva, N.V.; Gervas, P.A.; Litvyakov, N.V.; Stakcheeva, M.N.; Ponomaryeva, A.A.; Dobrodeev, A.Yu.; Denisov, E.V.; Belyavskaya, V.A.; Choinzonov, E.L. (Experimental Oncology, 2010)
Aim: To examine the influence of combined genotypes of TP53 (exon 4, intron 3, intron 6) and XRCC1 (codon 10) on lung cancer age of onset. Methods: TP53 polymorphisms in codon 72 of exon 4 (Arg72Pro), in intron 3 (16 bp duplication), in intron 6 (G/A transition) and XRCC1 polymorphism in codon 10 (Arg399Gln) were analyzed in blood cells of 177 lung cancer patients and 196 healthy donors with Restriction Fragment Lenth Polymorphism PCR. Results: We showed that combination of TP53 variant genotypes and XRCC1 variant genotype is associated with the increased lung cancer risk in younger, but not elderly, smokers. In contrast, wild allele combination increases lung cancer risk for individuals over the age of 60. Conclusion: Our data confirm antagonistic pleiotropy hypothesis indicating that p53 protects the organism against cancer early in life, but promoting aging phenotype, including late life cancer in older persons.